Are tearful individuals perceived as less competent? Probably not. Issue 2 (4th May 2018) - Zickfeld, Janis H.; van de Ven, Niels; Schubert, Thomas W.; Vingerhoets, Ad
ABSTRACT: What are the social signals of emotional tears? This question has fascinated scholars ever since Darwin. Studies have suggested several interpersonal effects of emotional tears. A recent article presented evidence in three studies that tearful individuals are not only perceived as warmer but also less competent than their non-tearful counterparts. However, the competence effect was relatively small, and a recent replication failed to find such an effect in two different populations while the warmth effect was replicated. This questions the generalizability of the effect of tears on perceived competence. To test whether individuals expressing emotional tears are really perceived as less competent and what boundary conditions such an effect might have, we specified a decision tree of three different studies in which we test differences between the original reference study and the replication. We replicated previous findings of the perceived (in)competence in Study 1 ( n  = 531) but observed a considerably smaller nonsignificant effect when proceeding to Study 2 ( n  = 471), which increased the number of stimuli. The earlier and now repeated replication failure can therefore likely be attributed to an increased variation in stimulus material. We conclude that there is not enough evidence to argue that one social outcome of tears signals a relative lack of competence as the effect seems to depend on the specific stimuli used.